2006
DOI: 10.1002/cphc.200500297
|View full text |Cite
|
Sign up to set email alerts
|

Berry Pseudorotation Mechanism for the Interpretation of the 19F NMR Spectrum in PF5 by Ab Initio Molecular Dynamics Simulations

Abstract: For the first time, theoretical evidence that confirms the importance of the Berry pseudorotation process in the interpretation of the 19F NMR spectrum of phosphorus pentafluoride (PF5) is presented. Ab initio molecular dynamics simulations have been performed to generate a large number of configurations used for NMR parameter computations at the density functional theory level. Two different temperatures were set to highlight the effect of pseudorotation process on the NMR spectrum. Average 19F chemical shift… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…14,36 In some cases, accuracy could be significantly improved by including dynamic effects by means of molecular dynamic simulations, for example, in order to extract a statistical ensemble of molecular structures that would be used for NMR calculation purposes. 16,18 Another puzzling result is the very poor accuracy observed within basis set I, i.e. when ECPs are used for carbon and oxygen atoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,36 In some cases, accuracy could be significantly improved by including dynamic effects by means of molecular dynamic simulations, for example, in order to extract a statistical ensemble of molecular structures that would be used for NMR calculation purposes. 16,18 Another puzzling result is the very poor accuracy observed within basis set I, i.e. when ECPs are used for carbon and oxygen atoms.…”
Section: Discussionmentioning
confidence: 99%
“…5 An agreement with 10-20% deviation from experiment is often considered as good. In principle, theoretical accuracy can be increased by taking into account influences on the magnetic shielding: solvent effect, motion of the nuclei, 16 molecular vibrations. Accurate computations of NMR parameters become feasible owing to the ability to describe the effect of the surroundings with various methodological strategies (QM/MM, continuum solvent methods, 17 molecular dynamics of the solvent network 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…A similar behaviour is expected for [Pb(CO) 5 ] 2+ : static studies have shown properties close to those of the tetracoordinated species. 3 External dynamic simulations on [Cu(H 2 O) 5 ] +38 and PF 5 39 have reported such inversions.…”
Section: The [Pb(co) 4 ] 2+ Complexmentioning
confidence: 95%
“…At sufficiently high temperature, proton spectra of fluxional compounds consist in the superposition of several bonding situations. A relevant, but computationally expensive, way to take into account the motion of protons consists in performing molecular dynamics (MD) simulations at the ab initio or DFT level of theory and to average the theoretical spectroscopic data [10][11][12] . We have developed in our group a Car-Parrinello MD (CPMD) code using atom-centered basis functions, which is a tool of choice for taking into account the role of temperature on the motion of nuclei 13,14 , and to calculate several properties with quantum chemistry methods more familiar to theoretical chemists.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of the Berry pseudorotation process in the interpretation of the 19 F NMR spectrum of phosphorus pentafluoride (PF 5 ) has been shown in Ref. 11. Ab initio MD (AIMD) simulations have been performed to generate a large number of geometries considered for NMR parameter computations at the DFT level.…”
Section: Introductionmentioning
confidence: 99%